Peran Dinas Kebudayaan Dan Pariwisata Dalam Pengelolaan Objek Wisata Pulau Camba Cambang Kabupaten Pangkep - Tina, Tina; Parawangi, Anwar; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aims to determine the role of the Culture and Tourism Office in the management of Camba Cambang Island tourism object in Pangkep Regency. The role of the Tourism Office as the manager of Camba Cambang Island, which acts as a motivator, facilitator, and dynamic in realizing an increase in tourists visiting and prospering the community around Tesebut Island. Therefore, with the role of the Tourism Office which is directly optimal and in-depth to develop the community. This type of research is a qualitative research with a descriptive approach where data obtained through observation, interviews and documentation. The informants in this study were four people including the head of the Pangkep district tourism office, the field of resource development, the field of tourism. The results showed that the role of the Office of Culture and Tourism in increasing the number of visitors of the Office of Tourism carried out various promotions through online media, events, exhibitions , banners and brochures. Increased motivation by training members in the community. The Office of Tourism empowers communities around the island by providing direction and socialization in makingsouvenirs.